2014
DOI: 10.1051/0004-6361/201322831
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric supergranular flows and magnetic flux emergence

Abstract: A recent study carried out on high-sensitivity SUNRISE/IMAX data has reported about areas of limited flux emergence in the quiet Sun. By exploiting an independent and longer (four hours) data set acquired by Hinode/SOT, we investigate these regions in more detail by analysing their spatial distribution and relation with the supergranular flow. Our findings, while confirming these calm areas, also show that the emergence rate of small magnetic elements is largely suppressed at the locations where the divergence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
(57 reference statements)
2
20
0
Order By: Relevance
“…Moreover, the study of the dynamics of the magnetic elements on the solar photosphere is of particular interest in astrophysics, since it could also provide constraints on a) the characteristic spatiotemporal scales of the emergence and diffusion processes of the magnetic field (e.g. Orozco Stangalini 2014); b) the rates of interaction between the magnetic elements themselves, which can cause magnetic reconnections and subsequent micro-flaring events: a plausible mechanism for the heating of the upper solar atmosphere (as in the model of Viticchié et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study of the dynamics of the magnetic elements on the solar photosphere is of particular interest in astrophysics, since it could also provide constraints on a) the characteristic spatiotemporal scales of the emergence and diffusion processes of the magnetic field (e.g. Orozco Stangalini 2014); b) the rates of interaction between the magnetic elements themselves, which can cause magnetic reconnections and subsequent micro-flaring events: a plausible mechanism for the heating of the upper solar atmosphere (as in the model of Viticchié et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This possibility appears even more attractive since high resolution observations have shown that small magnetic elements with diameters ∼100−150 km cover a significant fraction of the solar photosphere (Lagg et al 2010;Bonet et al 2012), although it has been shown that magnetic flux emergence is not homogeneous (Stangalini 2014).…”
Section: Introductionmentioning
confidence: 99%
“…32 This code was originally written for the identification and tracking of small-scale magnetic elements in the solar photosphere; [33][34][35] a task conceptually similar to that of the analysis of AO residual faint speckles in SHARK forerunner data. 36,37 In short, the code identifies and tracks, through sequential images, small-scale features that are above a user-specified threshold (4σ in our case), where σ is the standard deviation of the signal (intensity) computed in a dark region in the upper left corner of the image and covering at least an area of n pixels (where n ¼ 16 in our case). This implies that only structures with a size of the order of the PSF are identified and tracked, thus ruling out the possibility of including noise features.…”
Section: Speckle Lifetime Statisticsmentioning
confidence: 99%